The Great Degeneration : How Institutions Decay and Economies Die - Ferguson, Niall (London Penguin Books, 2012)
"What causes rich countries to lose their way? Symptoms of decline are all around us today: slowing growth, crushing debts, increasing inequality, aging populations, antisocial behavior. But what exactly has gone wrong? The answer, Niall Ferguson argues ... is that our institutions--the intricate frameworks within which a society can flourish or fail--are degenerating"--Dust cover flap.
Include Notes and Acknowledgements
Keywords: Developed countries -- Social conditions -- 21st Century -- Developed countries -- Economic conditions -- 21st Century -- Social institutions -- Developed Countries